2020
DOI: 10.1155/2020/7403128
|View full text |Cite
|
Sign up to set email alerts
|

Arabic Sentiment Analysis: A Systematic Literature Review

Abstract: With the recently grown attention from different research communities for opinion mining, there is an evolving body of work on Arabic Sentiment Analysis (ASA). This paper introduces a systematic review of the existing literature relevant to ASA. The main goals of the review are to support research, to propose further areas for future studies in ASA, and to smoothen the progress of other researchers’ search for related studies. The findings of the review propose a taxonomy for sentiment classification methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 89 publications
(116 reference statements)
0
51
0
Order By: Relevance
“…Feature selection (i.e., what the model receives as input) is another step toward building an accurate and generalizable model. N-Grams (i.e., the sequence of n-words) is an established featuring engineering technique in computational linguistics that is found to be popular and effective in Arabic semantic analysis applications (Ghallab, Mohsen, & Ali, 2020;Silva, Goncalves, & Cunha, 2016). This approach allows for models to learn both the individual words and the semantic relationship between multiple words.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feature selection (i.e., what the model receives as input) is another step toward building an accurate and generalizable model. N-Grams (i.e., the sequence of n-words) is an established featuring engineering technique in computational linguistics that is found to be popular and effective in Arabic semantic analysis applications (Ghallab, Mohsen, & Ali, 2020;Silva, Goncalves, & Cunha, 2016). This approach allows for models to learn both the individual words and the semantic relationship between multiple words.…”
Section: Methodsmentioning
confidence: 99%
“…These models allow for incorporating the uncertainty stemming out of the prior dataset distribution in contrast to the global or posterior distribution. In this proposal, Naï ve Bayes was utilized as it is the most commonly probabilistic supervised learning classification model used in Arabic sentiment analysis (Ghallab et al, 2020). The aforementioned Arabic sentiment dataset (Kaggle, 2019) was split into 47,000 and 11,000 Tweets for training and testing, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Norah Fahad Alshammari [19] Sentiment analysis classification for twitter data from Arabic to English with deep learning model. A complete review of Arabic sentiment analysis is given by Abdullatif Ghallab [20].…”
mentioning
confidence: 99%
“…Therefore, the complexity of analyzing tweets arises from the dialect differences and use of the new phrases among the young people. Also, since the Arabic language is spoken by different people from different countries and cultures (14) , there might be two different opinions about a person or an event based on the dialect that is used on the tweet even they use the same words. So, we might know the sentiment based on that.…”
Section: Data Collection and Preparation 21 Twitter Datamentioning
confidence: 99%
“…We explored a very helpful review paper about Arabic Sentiment Analysis ASA (14) , and we found couple studies that show a variance in the goals and results. That variance explained the difficulties in sentiment analysis using Arabic text, even the reviewed papers had applied different algorithms in different data sets.…”
Section: Introductionmentioning
confidence: 99%